Spheres of influence: Porphyromonas gingivalis outer membrane vesicles - Gui, M.J.; Dashper, S.G.; Slakeski, N.; Chen, Y.-Y.; Reynolds, E.C. (Molecular oral microbiology, 2016)
Summary Outer membrane vesicles (OMVs) are asymmetrical single bilayer membranous nanostructures produced by Gram‐negative bacteria important for bacterial interaction with the environment. Porphyromonas gingivalis, a keystone pathogen associated with chronic periodontitis, produces OMVs that act as a virulence factor secretion system contributing to its pathogenicity. Despite their biological importance, the mechanisms of OMV biogenesis have not been fully elucidated. The ~14 times more curvature of the OMV membrane than cell outer membrane (OM) indicates that OMV biogenesis requires energy expenditure for significant curvature of the OMV membrane. In P. gingivalis, we propose that this may be achieved by upregulating the production of certain inner or outer leaflet lipids, which causes localized outward curvature of the OM. This results in selection of anionic lipopolysaccharide (A‐LPS) and associated C‐terminal domain (CTD) ‐family proteins on the outer surface due to their ability to accommodate the curvature. Deacylation of A‐LPS may further enable increased curvature leading to OMV formation. Porphyromonas gingivalis OMVs that are selectively enriched in CTD‐family proteins, largely the gingipains, can support bacterial coaggregation, promote biofilm development and act as an intercessor for the transport of non‐motile bacteria by motile bacteria. The P. gingivalis OMVs are also believed to contribute to host interaction and colonization, evasion of immune defense mechanisms, and destruction of periodontal tissues. They may be crucial for both micro‐ and macronutrient capture, especially heme and probably other assimilable compounds for its own benefit and that of the wider biofilm community.